Digital Media Landscape in Brazil: Political (Mis)Information and Participation on Facebook and WhatsApp - Patricia Rossini; Érica Anita Baptista; Vanessa Veiga de Oliveira; Jennifer Stromer-Galley (Journal of Quantitative Description: Digital Media)
WhatsApp is one of the most used messaging platforms across the globe and is particularly prominent in the Global South. Despite being a private messaging app, WhatsApp is becoming an important platform for political information and political talk, which raises concerns about the spread of misinformation on the platform. This paper presents comprehensive descriptive results of a national survey of internet users in Brazil, focusing on political information on social media. Our data shows that Brazilians are very active social media users, particularly on Facebook and WhatsApp, and consider these platforms very important to fulfill a myriad of political and informational aims. However, they also demonstrate great concern about the quality and accuracy of information circulating online. Despite finding significant differences in how these two platforms are used, the data suggests that WhatsApp is becoming central to how Brazilians have access to and engage with politics.